Gastroesophageal reflux. - Yanet Hidalgo Marrero; Rafael Trinchet Soler; Lauro A. Melo Aguilera (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2005)
Although many infants has smaller degrees of gastroesophageal reflux, it is recognized that 1:3,000 at 1:10,000 of they have a pathological or symptomatic reflux. Near 90% of children vomits during the first 6 weeks of life, due primarily to the physiologic immaturity of antireflux mechanism. However, in 60% of cases, reflux disappears before 18 months, even without treatment. 30% maintains the symptoms, becoming in pathological, and of them, 10% develops serious problems, around 5% esophagitis with stenosis and between the 1 to 5% the death related with aspiration. We presented the Good Clinical Practices Guideline for Portal hypertension, approved by consensus in the 4th National Good Clinical Practices Workshop in Pediatric Surgery (Las Tunas, Cuba, March, 2005)